The Effects of Cognitive Therapy on Changes in Symptoms of Hallucinations in Schizophrenic Patients (Indian Journal of Public Health Research & Development, 2020)
Schizophrenia is a disease that affects various areas of individual function, including thinking, communicating,accepting, interpreting reality, feeling, and showing emotions. Non-pharmacological therapy given toovercome hallucinations of schizophrenic patients is cognitive therapy. The purpose of this study was todetermine the effect of cognitive therapy on changes in hallucinatory symptoms in schizophrenic patientsat Prof. Dr. M. Ildrem Mental Hospital in Medan. The design of this study is Quasi-Experimental OneGroup Pre and Post-test design, The study population was all hallucinatory patients with a total of 286 anda sample of 19 respondents. The sampling technique uses purposive sampling. Data collection tools usinga questionnaire that has been tested for validity. The statistical test used is the paired t test. The results ofthis study obtained the value of p = 0,000 (p
Keywords: hallucinations, schizophrenia, cognitive therapy, mental disorder